Technology commercialization primer - Buff, Eugene (Henry Stewart Talks, 2016)
Technology and technology transfer effectiveness, Product development timeline, Conflicting values and common interest, Formula for success, Different perceptions of technology value, Value proposition, Intellectual property, Key market differences, Deal preferences